Geochemical evidence from the Kioto Carbonate Platform (Tibet) reveals enhanced terrigenous input and deoxygenation during the early Toarcian - Han, Z; Hu, X; Hu, Z; Jenkyns, HC; Su, T (Elsevier, 2022)
The early Toarcian, as registered in a variety of sedimentary archives, was characterized by an abrupt negative carbon-isotope excursion (CIE) typically superimposed on a long-term positive trend, and was accompanied by significant climatic and environmental changes. However, the changes in continental weathering influx and oceanic deoxygenation in shallow waters and their possible role in causing carbonate-platform crises in low latitudes remains poorly constrained. Here, we present carbonate content and carbonate-hosted elements for the Pliensbachian–Toarcian transitional interval from the Kioto Carbonate Platform (KCP) in the Tibetan Himalaya. The most water-insoluble elements (e.g. Ti, Sc, Th and total rare earth elements) show an obvious increase starting at the Pliensbachian–Toarcian boundary, followed by a weak increase or relatively high-level values during the negative phase of the T-OAE CIE, suggesting that the enhanced terrigenous input can be linked to rapid global warming during this time interval. The Mn, Ce and Ce anomaly start to increase immediately following the rise in abundance of the water-insoluble elements, followed in turn by enhanced values over the interval of the negative CIE. These observations indicate that the deoxygenation process and development of manganous (suboxic) conditions occurred in shallow water during this time interval and were likely linked to enhanced continental weathering and nutrient input, favoring both primary productivity and oxygen consumption. Stratigraphically higher, the water-insoluble elements show a gradual decreasing trend parallel with elevated values of redox proxies during the recovery phase of the CIE, suggesting decline in continental weathering intensity and a corresponding second deoxygenation in shallow waters. In this instance, deoxygenation might have been caused by a slackening of ocean circulation and/or enhanced recycling of bioessential nutrients. The coupled relationship between biotic changes, carbonate content and geochemical data suggest that: (1) the onset of enhanced terrigenous influx and deoxygenation in shallow waters likely led to slight deterioration to the KCP around Pliensbachian–Toarcian boundary time, and (2) the drastically enhanced terrigenous flux and deoxygenation likely played a pivotal role in the more severe crisis for benthic carbonate producers during the negative phase of the CIE.